Management of Aesthetic Properties of Engravings Obtained Using Laser - M. Chernykh1, M.; E. Dryukova, A.; A. Ostanina, P.; V. Kargashina, E. (International Journal of Engineering and Technology, 2018)
The current paper discusses methods for managing the quality of engravings obtained using lasers. It is shown that in order to achieve a high aesthetic value of engravings it is necessary to adjust the layout with regard to the saturation of the tone of material and its tonal limit.Â Â Â